2020
DOI: 10.3390/nu12123909
|View full text |Cite
|
Sign up to set email alerts
|

Diet-Induced Obesity Disrupts Trace Element Homeostasis and Gene Expression in the Olfactory Bulb

Abstract: The aim of this study was to determine the impact of diet-induced obesity (DIO) on trace element homeostasis and gene expression in the olfactory bulb and to identify potential interaction effects between diet, sex, and strain. Our study is based on evidence that obesity and olfactory bulb impairments are linked to neurodegenerative processes. Briefly, C57BL/6J (B6J) and DBA/2J (D2J) male and female mice were fed either a low-fat diet or a high-fat diet for 16 weeks. Brain tissue was then evaluated for iron, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…Despite the impact of HFD on obesity and associated metabolic disorders being well-documented in the literature [ 28 , 29 , 30 ], the effects of probiotic Lact. rhamnosus LB1.5 supplementation on these parameters remains relatively understudied.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the impact of HFD on obesity and associated metabolic disorders being well-documented in the literature [ 28 , 29 , 30 ], the effects of probiotic Lact. rhamnosus LB1.5 supplementation on these parameters remains relatively understudied.…”
Section: Discussionmentioning
confidence: 99%
“…Under overweight and obesity conditions, brain homeostasis is impaired in both mammals and zebrafish [ 29 , 54 , 81 ]. We and others have previously demonstrated that DIO disrupts brain homeostasis by inducing BBB breakdown, cerebral oxidative stress and neuro-inflammation associated with impaired neurogenesis [ 29 , 39 , 40 , 53 , 54 , 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…11 Other authors have demonstrated that diet-induced obesity disrupts trace element homeostasis in various brain regions of mice in a sexspecific manner. 18,19 Furthermore, there is increasing evidence suggesting that adverse health effects triggered by the exposure to toxic heavy metals (e.g., cadmium, lead) may differ depending on sex, which could be attributed to differences in kinetics, mode of action, or susceptibility. 20 In this work, we studied the influence of sex in modulating metal metabolism in childhood obesity and IR.…”
Section: Introductionmentioning
confidence: 99%
“…However, Błażewicz et al interestingly found that the sex criterion may influence the association between metal contents and the BMI of children (e.g., negative correlation between BMI and blood Zn, plasma Cu, and urinary Fe among girls; positive correlation between BMI and plasma Co among boys) 11 . Other authors have demonstrated that diet‐induced obesity disrupts trace element homeostasis in various brain regions of mice in a sex‐specific manner 18,19 . Furthermore, there is increasing evidence suggesting that adverse health effects triggered by the exposure to toxic heavy metals (e.g., cadmium, lead) may differ depending on sex, which could be attributed to differences in kinetics, mode of action, or susceptibility 20 …”
Section: Introductionmentioning
confidence: 99%